Strategi Pengembangan dan Pemasaran Usaha Sablon Kaos “Esbe Clothing” di Kabupaten Bojonegoro - Budianto Budianto (Program Studi Ekonomi Pembangunan, 2026)
Abstract This community service program focuses on empowering women entrepreneurs in Desa Kepuharjo, Karangploso District, Malang Regency through social selling training. The program is a continuation of previous entrepreneurship training led by Ibu Zulaikah, where the group successfully started a brownie baking business. However, they face challenges in digital marketing knowledge and effective communication skills to build consumer relationships. The main problems are low understanding of digital marketing strategies, particularly in using social media to increase sales, and limited skills in effective communication with consumers. To address these issues, the program provides comprehensive training in social selling strategies, including digital platform utilization for product promotion. The methods include socialization, training, technology implementation, and continuous mentoring. The program successfully achieved significant outcomes: participants' digital marketing knowledge scores increased from 45% to 85%, 90% of participants demonstrated proficiency in creating quality visual content, and 100% established active online business accounts. Product innovation resulted in 3 new brownie flavor variants per participant, with an average 30-50% increase in monthly sales within the first three months. Through this training, women entrepreneurs in Desa Kepuharjo have become more economically independent and improved their family's quality of life.